Laser Treatment for Melanin Gingival Pigmentations: A Comparison Study for 3 Laser Wavelengths 2780, 940, and 445 nm - Manaf Taher Agha; Pavel Polenik (Hindawi Limited, 2020)
The normal appearance of the gingiva is pink to light red, and this appearance may change due to many factors and might be noticeable causing aesthetic concerns. In the Gulf area, the gingival melanin pigmentation is of the main type of concern, and patients expect the pigmentation to be removed for aesthetic reasons. Many techniques have been used to remove the melanin pigmentation such as using surgical blades, diamond or ceramic burs, chemicals, and lasers. This study is comparing the results of three lasers (Er, Cr, YSGG 2780 nm, Diode 940 nm, and 445 nm) in the removal of melanin gingival depigmentation. Clinical outcome parameters including bleeding, wound healing, pain, duration of procedure, color improvement, patient satisfaction, and relapse rate after 2 years were assessed. Conclusion. Within the limitation of this study, all three wavelengths were fast, effective in peeling the pigmentations and well tolerated by the patients. The esthetical results were excellent, and the patients were highly satisfied. Suggestion. To have a bigger number of samples in future papers, and histological studies might be included to explore the different impacts of each wavelength on the gingival melanin pigmentation specifically and on the gingival tissue generally.